Grundtvig og den middelalderlige kontemplative tradition - Pedersen, Kim Arne (Grundtvig-studier, 1993)
Grundtvig and the medieval 'kontemplative' traditionJørgen Pedersen: Prior omnium sapientia.Reviewed by Kim Arne Pedersen